Grado de microfiltración apical utilizando dos cementos selladores estudio comparativo In Vitro - Vidal Bazauri, Santos Maribel (2019)
ABSTRACT Objective: The aim of this study was to compare the grade of apical microfiltration of MTA ® and BIODENTINE ® cements used as an apical buffer in root canals. Material and Methods: We studied 30 dentais pieces divided into two groups of 15 pieces each. The ducts were instrumented simulating wide ducts with open apices, and sealed at this level placing an apical tampon of 5mm of cement sealer from apex to cervical, then sealed throughout its working length and sealed with conventional technique. Results: is demosting results obtained were analyzed to evaluate if there was a significant difference between the averages, the 95% student t test was used with a value of p< 0.05. Conclusions: demonstrating that there is no significant difference between grade of apical microfiltration of the sealant cements. mta and biodentine in straight and unique ducts.